Kegiatann Penelitian Dan Pengembangan Untuk Menemukan Pestisida Baru - Djumarman Djumarman (Jurnal Kimia dan Kemasan, 1987)
Developing a commercial pesticide is an expensive and time consuming process. Moving a single product from the discovery phase to the market place can take a decade of work and will cost many millions of dollars before the additional tens of millions needed to design and build a production facilities. A significant portion of the research and development process is testing to determine that the product works againts the pests it was made to control. Part of this process is balancing the expenses of using the pesticide again ts the market value of the resulting increased crop yield.